Considering Indigenous Environmental Issues in Canadian Curricula: A Critical Discourse Analysis - Lowan-Trudeau, Gregory; Fowler, Teresa (Journal of the Canadian Association for Curriculum Studies, 2021)
This article presents insights from a curricular review of Canada’s ten provinces and three territories with a focus on critical Indigenous environmental issues. This inquiry was conducted amidst nationally prominent events and socio-ecological movements such as the Truth and Reconciliation Commission, Idle No More and numerous oil and gas pipeline protests. We share findings revealed through this review informed by Eisner’s (2002) three curricula—the explicit, implicit and null—and a qualitative critical discourse analysis methodology.